Mitochondrial dysfunction in heart diseases: Potential therapeutic effects of Panax ginseng - Cao, Xinxin; Yao, Fan; Zhang, Bin; Sun, Xiaobo (Frontiers in Pharmacology, 2023)
Heart diseases have a high incidence and mortality rate, and seriously affect people's quality of life. Mitochondria provide energy for the heart to function properly. The process of various heart diseases is closely related to mitochondrial dysfunction. Panax ginseng (P. ginseng), as a traditional Chinese medicine, is widely used to treat various cardiovascular diseases. Many studies have confirmed that P. ginseng and ginsenosides can regulate and improve mitochondrial dysfunction. Therefore, the role of mitochondria in various heart diseases and the protective effect of P. ginseng on heart diseases by regulating mitochondrial function were reviewed in this paper, aiming to gain new understanding of the mechanisms, and promote the clinical application of P. ginseng.